Posterior sagittal anorectoplasty (PSARP). A new approach for treating anorectal malformations. - Dawood, Nawfal. S.; yahya, Kutiaba (Journal of the Faculty of Medicine Baghdad, 2007)
Background:-Anorectal malformation is a congenital anomaly of different varieties and its correction needs good experience , knowledge about this varieties and specific surgical tools, otherwise the child may lose his the only chance to live normally without disastrous complication like incontinence. Objective:-assessment of the advantage of this procedure in management of anorectal malformations and the percentage for anal continence. Patients and methods:-. This study was carried out in the child’s central teaching hospital in Baghdad total number (70) cases were included in the study, 37 males and 33 females: aged 7 days to 6 years. They attended the hospital between October 1998-october 2004. Male defect included: 1) Low type ....5 cases No colostomy needed. 2) Intermediate type.... 23 cases. needed colostomy 3) High type.... 9 cases needed colostomy. • Female defects: 1) Imperforate anus with vestibular fistula—31 cases. 2) Imperforate anus without fistula 2 cases. Results: From the study we gain the following results:- all the male patients with low and intermediate types 28 cases (40%) show 100% continence. All female patients with imperforated anus with vestibular fistula and without fistula 33 cases (47%) show 100% continence. The combination of male and female patients show 61 patients of 70 show 100%continence in a percentage of 87%. The nine cases (12.85%) with recto bladder neck fistula show poor continence due to their bad sacral contour associated with the poor development of pelvic muscles sphincter. This result was revealed from follow-up together with the presence of external sphincter muscle contraction which occurs during digital PR examination or by the use of surgical dilators. Conclusion: From the study we found that this procedure gives high percentage of continence and should be used instead of other procedures.